Multiple factors associated with nest-site selection in a wetland-specialist, the Wren-like Rushbird (Phleocryptes melanops). (2nd October 2019) - Chiaradia, Nicolás Mariano; Isacch, Juan Pablo; Pretelli, Matías Guillermo; Cardoni, Daniel Augusto
ABSTRACT: Diverse factors may limit nest-site selection; however, nest predation has long been considered a main factor driving nest-site selection in birds. Marsh-nesting birds face a particularly important trade-off between habitat features that impede their vision of the approach of potential predators and nest concealment from predators. Here, we analyse how different ecological variables influence nest-site selection in the habitat-specialist Wren-like Rushbird ( Phleocryptes melanops ) breeding in three different wetlands of the Pampas region of Argentina over 3 years. Rushbirds selected nest sites with higher heights and denser vegetation, compared to random sites. Nest height was positively associated with vegetation height and lower visibility from the point of view of aerial predators, and the nest entrance was oriented towards the region with greatest visibility of the nest from the point of view of Rushbirds. Rushbirds seem to flexibly adjust their nest location in response to high predation risk, building their nests under structures built by other birds when breeding colonies of herons and gulls (potential nest predators) are present. Initial nest-site selection is performed by males, which then attempt to attract females to a rudimentary nest. Females sometimes reject such sites and the male then selects a new nesting location. Our study highlights the potential for flexible sex differences in nest-site selection.